2018
DOI: 10.1038/ijo.2017.308
|View full text |Cite
|
Sign up to set email alerts
|

An OLTAM system for analysis of brown/beige fat thermogenic activity

Abstract: BACKGROUND/OBJECTIVESThermogenic fat is present in humans and emerging evidence indicates that increasing the content and activity of these adipocytes may lead to weight loss and improved metabolic health. Multiple reporter systems have been developed to assay thermogenic fat activity based on the transcriptional and translational activation of Ucp1, the key molecule that mediates nonshivering thermogenesis. Our study aims to develop a much-needed tool to monitor thermogenic fat activity through a mechanism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We wish to emphasize that all Ucp1 reporter mouse models published so far, including our new model, are suitable to monitor Ucp1 gene expression but do not report on thermogenic activity of UCP1 [44], [45], [46]. The real thermogenic activity and total capacity can be assessed with indirect calorimetry [47], [48] and new emerging technologies [49], [50], [51].…”
Section: Discussionmentioning
confidence: 99%
“…We wish to emphasize that all Ucp1 reporter mouse models published so far, including our new model, are suitable to monitor Ucp1 gene expression but do not report on thermogenic activity of UCP1 [44], [45], [46]. The real thermogenic activity and total capacity can be assessed with indirect calorimetry [47], [48] and new emerging technologies [49], [50], [51].…”
Section: Discussionmentioning
confidence: 99%
“…Knockout cells were verified by sequencing. The PHD enzyme activity luciferase reporter was previously described (46). Briefly, FPN GFP cells were infected at 10 MOI overnight and treated the next day with 250 ng/ml doxycycline, 100 μM FG4592 (Selleckchem), 200 μM ferric ammonium citrate (FAC) (Sigma-Aldrich), and/or 1 mg/ml human recombinant hepcidin (Bachem) or 200 μM DFO (Sigma-Aldrich).…”
mentioning
confidence: 99%
“…1E). Given the increased Ucp1 expression, we examined if TC‐E treatment increases thermogenesis of the cells using OLTAM [ODD‐Luc (luciferase fused with the oxygen‐dependent degradation domain)‐based Thermogenic Activity Measurement] system that we recently developed and reported to measure thermogenic activity of brown or beige adipocytes [14]. The result showed that TC‐E treatment increased ODD‐Luc activity to a level comparable with that observed following ISO treatment, suggesting that TC‐E enhances thermogenesis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human adipose precursor cells isolated from the SQ fat were obtained as previously described [14]. All specimens were collected under the protocols reviewed and approved by the University of Michigan Medical School Institutional Review Board (IRBMED).…”
Section: Methodsmentioning
confidence: 99%